2019
DOI: 10.1140/epjc/s10052-019-7119-3
|View full text |Cite
|
Sign up to set email alerts
|

Fitting the b-quark PDF as a massive-b scheme: Higgs production in bottom fusion

Abstract: We show that a simple and accurate approach to the computation of hadron collider processes involving initial-state b quarks can be obtained by introducing an independently parametrized b PDF. We use the so-called FONLL method for the matching of a scheme in which the b quark is treated as a massless parton to that in which it is treated as a massive state, and extend it to the case in which the b quark PDF is not necessarily determined by perturbative matching conditions. This generalizes to hadronic collisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
4
7
0
Order By: Relevance
“…The latter issue has instead recently been resolved [8]. Indeed it has been shown that a 5F massive scheme 1 can be consistently construct by simply constructing a parametrised b-PDF, and performing the FONLL matching between the 4FS and the 5FS: the matched FONLL result is indeed identical to what is defined in Ref.…”
mentioning
confidence: 85%
“…The latter issue has instead recently been resolved [8]. Indeed it has been shown that a 5F massive scheme 1 can be consistently construct by simply constructing a parametrised b-PDF, and performing the FONLL matching between the 4FS and the 5FS: the matched FONLL result is indeed identical to what is defined in Ref.…”
mentioning
confidence: 85%
“…[19] for a methodology based on the idea of vetoing -hadrons, and to Refs. [20,21], for the formulation of a massive 5FS with consistent -quark PDFs to be used in association with massive initial states [22]. A promising avenue for matching 4FS and 5FS at the level of exclusive observable is based on multi-jet merging: the simulations in the 5FS are merged with the calculations of the production of -quark associated final states in the 4FS [23].…”
Section: Maria Ubialimentioning
confidence: 99%
“…Alternatively one can develop a scheme which combines these approaches, providing a uniform description of the scattering process across arbitrary energy scales-such a description is provided by a massive variable flavour number scheme. This topic has been studied in various contexts in the past [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and with particular focus on the process of lepton-nucleon scattering [22][23][24][25][26][27][28][29][30][31]. In the latter case, it is well understood how to apply such a formalism to the description of nucleon structure functions.…”
Section: Introductionmentioning
confidence: 99%